2021
DOI: 10.48550/arxiv.2108.04560
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intent-driven autonomous network and service management in future cellular networks: A structured literature review

Kashif Mehmood,
Katina Kralevska,
David Palma

Abstract: Intent driven networks are an essential stepping stone in the evolution of network and service management towards a truly autonomous paradigm. User centric intents provide an abstracted means of impacting the design, provisioning, deployment and assurance of network infrastructure and services with the help of service level agreements and minimum network capability exposure. The concept of Intent Based Networking (IBN) poses several challenges in terms of the contextual definition of intents, role of different… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Lastly, we will consider integrating into the CIM software innovative solutions such as intent-based networking [31] for defining communication requirements that the RPA network is assumed to deliver.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, we will consider integrating into the CIM software innovative solutions such as intent-based networking [31] for defining communication requirements that the RPA network is assumed to deliver.…”
Section: Discussionmentioning
confidence: 99%
“…Although the earliest work on IDNM is focused on fixed networks, the most recent ones [88,89,90] have focused on IDNM for mobile networks as well. Very detailed and comprehensive structural reviews on this topic are covered in [91,92]. In [91] the authors went beyond the scope of mobile networks to focus on generic intent-driven systems where the proposed system is expected to be utilized in the context of business support systems.…”
Section: Related Literaturementioning
confidence: 99%
“…In [92] the authors analyzed the IBN methods proposed in [88,89,90], identifying a number of shortcomings in those methods. They observed that the existing work missed at least one of the four core research areas: (i) processing and life cycle, (ii) orchestration and management, (iii) use-cases analysis and (iv) an architecture framework for intent-driven networks.…”
Section: Related Literaturementioning
confidence: 99%
“…Although the earliest work on IDM is focused on ixed networks, the most recent ones [7,8,9] have focused on IBN for mobile networks as well. Very detailed and comprehensive structural reviews on this topic are covered in [10,11]. In [10] the authors went beyond the scope of mobile networks to focus on generic intent-driven systems where the proposed system is expected to be utilized in the context of business support systems.…”
Section: Surveysmentioning
confidence: 99%
“…In [11] the authors analyzed the IBN methods proposed in [7,8,9], identifying a number of shortcomings in those methods. They observed that the existing work missed at least one of the four core research areas: (i) processing and life cycle, (ii) orchestration and management, (iii) use-cases analysis and (iv) an architecture framework for intent-driven networks.…”
Section: Surveysmentioning
confidence: 99%